Legal and Political Aspects of Iron Fertilisation in the Southern Ocean: Implications of Australian Involvement - Jabour, JA (IOS Press, 2002)
CO2 sequestration in the deep oceans is a natural process and the Southern Ocean is the world's major atmospheric CO2 reservoir. Recently, small-scale open-ocean iron fertilisation experiments were conducted in selected high nutrient low chlorophyll-a (HNLC) areas to verify the 'iron hypothesis'.2 In the process, it was discovered that there might be a potentially beneficial dual application for iron fertilisation. The research found that fertilisation enhanced the natural sequestration process by promoting phytoplankton biomass - one critical component of the biological pump which intrinsically draws down atmospheric CO2 to the deep ocean during the photosynthetic process. In addition, it was thought that the resulting phytoplankton bloom might, under optimum circumstances, increase oceanic biological productivity by proving a richer food source throughout all trophic levels. However, the science should be treated with caution because it is new, complex and also to a certain degree contentious.3 Neither its efficacy nor its consequences regarding CO2 sequestration or enhanced productivity are well understood. This article reviews what little is known about the process so far and makes some observations about the likely legal and political aspects that would need to be addressed should the science evolve into commercial activity.